Measuring Implicit and Explicit Knowledge in Second Language Research. Issue 3 (18th April 2013) - Rebuschat, Patrick
<x xml:space="preserve">Abstract</x> This article reviews three types of measures which have been widely used in psychological research to assess the conscious or unconscious status of knowledge: retrospective verbal reports, direct and indirect tests, and subjective measures. The goal is to make these techniques available to a wide audience of second language (L2) researchers and to offer suggestions for their sound use in order to promote the study of implicit L2 learning. Each section begins with a brief definition of what it means to have acquired unconscious (implicit) knowledge according to the measure in question. This is followed by a description of representative studies that illustrate how the technique has been used and by a discussion of its limitations. Each section concludes with specific guidelines on how to apply the respective measure to the investigation of implicit and explicit L2 learning.